TMIC-74. THERAPEUTICALLY REPROGRAMMING MICROGLIA TO ANTI-TUMORAL ACTIVATION STATES IN DIFFUSE MIDLINE GLIOMA, H3K27 MUTANT. (14th November 2022) - Keane, Lily; Perez, Mercedes Posada; Friess, Lara; Joseph, Bertrand
Abstract: Diffuse midline glioma (DMG), H3K27M mutant, is one of the most challenging paediatric cancers to date with poor treatment options and dismal survival outcomes. Therefore, new treatment options are desperately needed. Previously we found that activation of the microglial tumour-supportive phenotype by DIPG is associated with a transient H3K27me3 downregulation suggesting a role for this pathway in inducing this activation state. However, it should be noted, that microglia do not carry the H3-K27M mutation when analysed in DIPG patient tissue, otherwise characteristic of the cancer cells. Ezh2 is a histone methyltransferase and the catalytic subunit of the polycomb repressor complex 2 (PRC2), responsible for tri-methylation of histone H3 at lysine 27. We found that repression of Ezh2 in microglia induced an anti-tumour phenotype resulting in decreased cancer cell invasion capability, increased microglial phagocytosis, and tumour-related cell death. Antisense RNA strategies were used to target Ezh2 gene expression in BV2 microglia and we have now carried out RNA sequencing on scramble BV2 or si Ezh2 microglia co-cultured with DIPG tumour cells to further understand how EZH2, PRC2 and H3K27me3 regulates DIPG-induced microglia activation. Further work has found that activation of the microglial tumour supportive phenotype, in this context, is determined by a complex epigenetic mechanism involving both H3K4me3 and H3K27me3 and their associated methyltransferases. These histone marks are often associated with bivalent regulation of distinct gene transcription programs, and we are currently investigating if this is the case for DIPG-induced activation states using chromatin immunoprecipitation techniques. Overall, our results indicate that microglia, can be reprogrammed epigenetically by EZH2 inhibition to exert anti-tumoral responses and that microglia represent a new therapeutic avenue in DIPG. This future work should provide novel mechanisms governing pro-tumoral microglial activation states and new therapeutic targets that can be combined with EZH2 inhibition to enhance anti-tumoral microglia activation states.